Концептуальне бачення смарт-енергосистеми - Serdiuk, Oleksandr S.; Andriienko, Bohdan Ya. (Institute of Industrial Economics of NAS of Ukraine, 2024)
In modern scientific and political circles, the smart energy system is considered as an integral component of Industry 4.0, since in a broad sense it serves the purpose of increasing production efficiency due to the introduction of artificial intelligence technologies. However, currently there is no single, established vision regarding the meaning of the term "smart energy system". As a rule, it is viewed through the prism of separate, often unrelated technological processes, which complicates the development of consistent theoretical provisions and practical recommendations for the development of Industry 4.0.The purpose of the article is the systematization of scientific views on certain aspects of the application of digital technologies in the field of energy and the development of a holistic conceptual vision of a smart energy system.The key elements of the smart energy system consist of smart energy generation, as a set of digitalization measures for the control system of energy generating facilities, aimed at increasing the specific production of electricity, as well as adjusting the load within the nodes of electricity production from renewable sources with the aim of stabilizing the energy flow; smart synchronization, which is designed to distribute the load among the energy sectors on the basis of an intelligent assessment of system needs and capabilities; smart distribution, which optimizes the operation of distribution networks based on data analysis of temporal and spatial trends in the electricity transmission system; and smart consumption, which involves the implementation of technological measures that create conditions for economical consumption of electricity.The holistic vision of the "smart energy system" concept, which provides for the comprehensive implementation of measures provided for by the micro-concepts of smart energy generation, smart synchronization, smart distribution and smart consumption, is substantiated. It is argued that the implementation of the “smart energy system” concept will ensure a synergistic effect of economical utilization of energy resources.